2019
DOI: 10.1039/c8nr06888g
|View full text |Cite
|
Sign up to set email alerts
|

3-Arm star pyrene-functional PMMAs for efficient exfoliation of graphite in chloroform: fabrication of graphene-reinforced fibrous veils

Abstract: Stable graphene dispersions in chloroform, using very low pyrene-functionalized polymer/graphite mass ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 65 publications
6
12
0
Order By: Relevance
“…All scaffold types exhibited typical yield behavior. An analogous behavior was also observed in [28] and in [43], in which Poly(methyl methacrylate) (PMMA) and SP scaffolds were fabricated and tested under the same conditions. Bar charts of Figure 8A-E provide average values of the apparent E, σ max , ε max (%), σ y , and ε y (%) respectively.…”
Section: Mechanical Propertiessupporting
confidence: 61%
See 2 more Smart Citations
“…All scaffold types exhibited typical yield behavior. An analogous behavior was also observed in [28] and in [43], in which Poly(methyl methacrylate) (PMMA) and SP scaffolds were fabricated and tested under the same conditions. Bar charts of Figure 8A-E provide average values of the apparent E, σ max , ε max (%), σ y , and ε y (%) respectively.…”
Section: Mechanical Propertiessupporting
confidence: 61%
“…Thus, nanofillers' inclusion contributed to electrostatic charge build up during SEP. Finally, the quite large SSD values are common in electrospinning technique [28,43] as small changes of the electric field occur during the phenomenon. Apart from SEM examination of the fabricated PEI scaffolds, TEM examination was also conducted (see Figure 5B).…”
Section: Structural and Morphological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of scaffolds modified with HAP, it was shown that by increasing the HAP concentration the tensile properties were enhanced even if the aggregate presence is made stronger by increasing the HAP concentration (see in Figure 4 A,B). Similar findings were also observed in Kostopoulos et al’s [ 30 ] and Gkermpoura et al’s [ 38 ] investigations, in which various scaffolds were nanomodified with various nanoparticles. In Figure 8 , a snapshot of the tensile testing is illustrated, indicated the ductile nature of the precise PLA scaffolds.…”
Section: Resultssupporting
confidence: 90%
“…GNPs can be obtained by using different methods. These methods involve mechanical and/or chemical exfoliation of graphite [21,25,26].…”
Section: Introductionmentioning
confidence: 99%